Effects of Crowding and Water Flow on Golden Shiners Notemigonus crysoleucas, Held in a Flow Tank - Kaimal, Sindhu; Haukenes, A. H.; Renukdas, Nilima N.; Kelly, Anita M. (Frontiers in Physiology, 2022)
Split-pond systems (SPS) such as those used for catfish are being considered for raising baitfish. When using these systems for baitfish such as golden shiners Notemigonus crysoleucas, an important factor to be considered is how well the species can tolerate crowding, as the design mandates fish be confined to a smaller portion of the pond. Another aspect of the SPS design is the water flow between the two units for at least 10–14 h each day. SPS can be successfully implemented for other species if factors such as crowding, and water flow do not affect growth. Two laboratory studies were conducted each using 12, 40-L tank flow-through system to observe the growth and physiological performance of golden shiners held for 28 days at three crowding densities: 600; 1,200, and 2,400 fish/m3, keeping water flow at 1 cm/s (Experiment 1) and using three flow rates: 1, 2, and 4 cm/s at similar densities (600 fish/m3) (Experiment 2). At the end of the experiments, fish were subject to acute 1-min confinement stress and whole-body cortisol was measured at 30 min intervals for up to 2 h to monitor the secretion pattern and recovery. Results from experiments showed no difference in the final weight, length, feed conversion, and survival among treatment groups; survival rates were lower in the flow study because of columnaris Flavobacterium covae infections. Baseline cortisol was also not different among the treatments. Cortisol increased 30 min after the acute stress and returned to near baseline in 2 h in the crowding study suggesting acclimation to the chronic stressor. However, in the flow study, cortisol remained elevated even after 2 h, and hence a compromised pathophysiological response. Crowding and water flow do not impair feed intake, growth, or survival in golden shiners, and in these aspects may be a suitable species for SPS.